Do simulated molecular clouds look like real ones?. Issue 4 (13th January 2023) - Priestley, F D; Clark, P C; Whitworth, A P
ABSTRACT: Simulations of molecular clouds often begin from highly idealized initial conditions, such as a uniform-density sphere with an artificially imposed turbulent velocity field. While the resulting structures may appear qualitatively similar to those detected in continuum and line observations, it is unclear whether they are genuinely representative of real molecular clouds. Recent observational work has discovered a tight, often close-to-linear relationship between the integrated intensity of molecular lines and the total column density of the cloud material. We combine magnetohydrodynamical simulations, time-dependent chemistry, and radiative transfer to produce synthetic molecular line observations of model clouds. We find similarly tight correlations between line intensity and column density to those observed, although the linear behaviour is only seen in isolated (as opposed to colliding) model clouds. This linear relationship is not due to optically thin emission; all lines investigated have high optical depths, and the increase in integrated intensity with column density is due to higher velocity dispersion along the line of sight. Overall, the idealized models commonly used in the literature appear to be reasonably accurate representations of real molecular clouds.